A mitochondrial-targeted ubiquinone modulates muscle lipid profile and improves mitochondrial respiration in obesogenic diet-fed rats. Issue 7 (9th February 2016) - Coudray, Charles; Fouret, Gilles; Lambert, Karen; Ferreri, Carla; Rieusset, Jennifer; Blachnio-Zabielska, Agnieszka; Lecomte, Jérôme; Ebabe Elle, Raymond; Badia, Eric; Murphy, Michael P.; Feillet-Coudray, Christine
Abstract: The prevalence of the metabolic syndrome components including abdominal obesity, dyslipidaemia and insulin resistance is increasing in both developed and developing countries. It is generally accepted that the development of these features is preceded by, or accompanied with, impaired mitochondrial function. The present study was designed to analyse the effects of a mitochondrial-targeted lipophilic ubiquinone (MitoQ) on muscle lipid profile modulation and mitochondrial function in obesogenic diet-fed rats. For this purpose, twenty-four young male Sprague–Dawley rats were divided into three groups and fed one of the following diets: (1) control, (2) high fat (HF) and (3) HF+MitoQ. After 8 weeks, mitochondrial function markers and lipid metabolism/profile modifications in skeletal muscle were measured. The HF diet was effective at inducing the major features of the metabolic syndrome – namely, obesity, hepatic enlargement and glucose intolerance. MitoQ intake prevented the increase in rat body weight, attenuated the increase in adipose tissue and liver weights and partially reversed glucose intolerance. At the muscle level, the HF diet induced moderate TAG accumulation associated with important modifications in the muscle phospholipid classes and in the fatty acid composition of total muscle lipid. These lipid modifications were accompanied with decrease in mitochondrial respiration. MitoQ intake corrected the lipid alterations and restored mitochondrial respiration. These results indicate that MitoQ protected obesogenic diet-fed rats from some features of the metabolic syndrome through its effects on muscle lipid metabolism and mitochondrial activity. These findings suggest that MitoQ is a promising candidate for future human trials in the metabolic syndrome prevention.